PERLINDUNGAN HUKUM BAGI KONSUMEN ATAS MALPRAKTIK JASA PEMASANGAN BEHEL PADA TUKANG GIGI - I Gusti Agung Janitra Nareswari Putri; Ni Ketut Supasti Dharmawan (Kertha Negara : Journal Ilmu Hukum, 2023)
The number of dental services that carry out their work exceeds the legal limits. However, there are still many who seek treatment at the dentist due to social inequality. Frequent deviations have an impact on service users in terms of assets and others. The owner of the health practice is not responsible. The purpose of this study was to determine the protection for consumers in the event of malpractice of dental artisans and to find out the sanctions against malpractice of dental artisans that harm consumers. Analysis of legal materials uses extensive and restrictive interpretations, namely expanding and narrowing the meaning of a law, while also using descriptive analysis, namely the presentation of research results. The results of the study indicate that the legal regulation of consumer protection against dental artisan malpractice which is regulated in the Consumer Protection Act, the rights of every consumer in Article 4. and authority. Meanwhile, legal sanctions for perpetrators are divided into 3, namely administrative, civil and criminal sanctions. Therefore, the government needs to carry out a routine monitoring of cases like this in the field directly. Keywords: Dentist, Malpractice, Legal Protection